Die GfM als gesamtdeutsche Gesellschaft - Klingberg, Lars (Die Musikforschung, 2023)
The “Gesellschaft für Musikforschung” (GfM) was, from its foundation until 1968, the professional representation of musicologists in all German occupation zones and of both German states. Since the establishment of the branch office in Leipzig (1954), the GfM was politically instrumentalized by the GDR party and state apparatus as well as by musicologists loyal to the SED. The most important goal was the creation of two sections representing East and West Germany respectively; alternatively, the foundation of a separate musicological society in the GDR was prepared. These efforts were intensified after the construction of the Berlin Wall (1961). A central role was played by Karl Laux, the director of the Dresden Music Academy, and a personal friend of GfM president Friedrich Blume. Following a decision of the Secretariat of the Central Committee of the SED on April 5, 1967, the GfM finally had to end its activities in the GDR in September 1968, and East-German musicologists joined the “Verband Deutscher Komponisten”.